2017
DOI: 10.1089/tmj.2017.0009
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Malignant Melanoma in Store-and-Forward Teledermatology

Abstract: Diagnosis and management of melanoma in SFT is comparable to FTF care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 15 publications
1
19
1
Order By: Relevance
“…Melanoma is a multifactorial tumor arising from an interplay between environmental exposure and genetic susceptibility 4 , and UV exposure is considered to be the most important risk factor 5 . Early detection and timely treatment of melanoma are considered to be the two most critical factors in reducing mortality 6 . Compared to other tumors, melanoma has the advantage of cutaneous location, which allows its early detection.…”
Section: Introductionmentioning
confidence: 99%
“…Melanoma is a multifactorial tumor arising from an interplay between environmental exposure and genetic susceptibility 4 , and UV exposure is considered to be the most important risk factor 5 . Early detection and timely treatment of melanoma are considered to be the two most critical factors in reducing mortality 6 . Compared to other tumors, melanoma has the advantage of cutaneous location, which allows its early detection.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review found the diagnostic accuracy of face‐to‐face dermatology consultation (67%–85% agreement with reference standard, Cohen Îș , 0.90) was higher than teledermatology (51%–85% agreement with reference standard, Cohen Îș , 0.41–0.63) for the diagnosis of skin cancer (Finnane et al., 2017). For melanoma specifically, in a cohort study of 7,960 veterans among whom 61 melanomas were detected, store‐and‐forward teledermatology readers correctly diagnosed 45 (74%) and managed 57 (93%) lesions, which was comparable to published rates of face‐to‐face accuracy (Wang et al., 2017).…”
Section: Teledermatologysupporting
confidence: 63%
“…Teledermatology and teledermoscopy demonstrates good accuracy when provided via video consultations (real-time) or transmitting via store-and-forward still digital macro or dermoscopy images, or hybrid combinations of both. 3–5 Teledermatology has been evaluated for skin cancer early detection, lesion follow-up, and many other skin conditions such as rashes and wounds, 6 and diagnosis and monitoring of acne 7 and psoriasis. 8 Teledermatology services have consistently demonstrated reduced waiting times for assessment and diagnosis, 9 increased access to services in rural and remote areas 10 and high patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%